SOULMATE CARD GAME FOR HUMANIST ECONOMIC LEARNING IN THE DISRUPTION ERA - Anisaurrohmah; Muhammad Nur (Indonesian Journal of Education (INJOE), 2022)
The use of attractive media can overcome the passivity of students. Card games are not something strange in the daily lives of students, but unfortunately they are rarely designed for learning activities. Even for teenagers, the game can easily be played with friends. The cards that are often played are like Bridge, Uno, Tarot, Rummy and others. Based on these descriptions, the authors try to create an innovative learning media named "Soulmate Card". This media is very flexible to be applied to other economic materials or to other subjects. So this learning innovation is entitled "Soulmate Card Game for Humanist Economic Learning in the Era of Disruption". This research is a classroom action research that uses quantitative descriptive analysis techniques because it uses measurements to determine the percentage of learning implementation and student learning result. The subjects were teachers and students of 10th grade of social class MAN Insan Cendekia Tanah Laut, that Consist of 25 student with 12 male and 13 female. Soulmate Card is a development of flash cards. In Soulmate Card students are invited to find a pair of question cards (questions) held by the teacher. If their partners meet, they are called "Soulmate". When do not find a partner, students must take the "No" card contains other questions that will be answered by students who read the "No" card or throw it to other students. If it`s true, then students who answer correctly will take the "Yes" card and must read aloud the information written on the "Yes" card. For soulmate card games, it takes 85 minutes. The opening and pretesting are about 20 minutes, delivery of additional information for 10 minutes, final test and closing are in 20 minutes. Observation results show that students actively participate in learning, learning activities seems fun, good student literacy and no students fall asleep in class. This habit of learning can increase the activeness of students to make social interaction better. Good social interaction can realize humanist  learning activities, namely the realization of a better social life. Based on an analysis of student learning result classically in cycle 1 was 82.4 while in cycle 2 was 90.1. The Increasing of average student learning result show that economic learning with soulmate card games can improve student learning result.